PHA coating film as well as preparation method and application thereof
By leveraging the synergistic effect of composite nanoparticles and microspheres, the mechanical properties and water resistance of PHA coated films are improved, solving the problems of insufficient performance, complex preparation, and high cost in existing technologies, and realizing the preparation of high-performance and low-cost PHA coated films.
Patent Information
- Application Number
- CN202510990814.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-18
- Publication Date
- 2025-10-28
AI Technical Summary
Existing PHA coated films are unsatisfactory in terms of mechanical properties, water resistance, processing performance, and compatibility. Moreover, their preparation processes are complex and costly, making it difficult to meet the needs of food and industrial packaging.
By mixing composite nanoparticles and composite microspheres in a ratio of 3 to 5:1, the mechanical properties and water resistance of the PHA coating film are improved through the combined effect of nano-reinforcement and microsphere toughening, while ensuring the processing stability and biocompatibility of the material.
It significantly improves the tensile strength, elongation at break, and water resistance of PHA coated films, enhances component compatibility and processing stability, meets green environmental protection standards, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable materials technology, specifically relating to a PHA coated film, its preparation method, and its application. Background Technology
[0002] Under the global trend of environmental protection, biodegradable polymer materials have become the main direction for replacing traditional petroleum-based plastics. PHA, as a biodegradable material, has shown great potential in packaging, agricultural films, and other fields. However, existing PHA-coated films have poor mechanical properties and insufficient water resistance. At the same time, their preparation process is complex and the production cost is high. Pure PHA films are difficult to meet the high requirements for material strength and toughness in food packaging and industrial packaging. These factors seriously limit their widespread application in practice.
[0003] Meanwhile, the polar groups in the PHA molecular chain result in poor water resistance, making it prone to moisture absorption in humid environments, leading to a decline in the dimensional stability and mechanical properties of the membrane material. In terms of processing performance, PHA has a narrow melting temperature range and a small processing window, making it susceptible to thermal degradation due to improper temperature control, resulting in material performance deterioration. PHA also exhibits poor compatibility with other commonly used resins; simple blending can lead to phase separation in composite membranes, significantly reducing the mechanical properties and weather resistance of the membrane material. Existing PHA coating membrane preparation processes are complex, involving multiple cumbersome steps, resulting in high production costs and insufficient market competitiveness. Therefore, solving the problems of mechanical properties, water resistance, processing performance, and component compatibility of PHA coating membranes through innovative material design and modification technologies, and developing high-performance, simple, and cost-effective PHA coating membranes, has become a key technical challenge urgently needing breakthroughs in this field. Summary of the Invention
[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a PHA coating film, its preparation method, and its application. The method involves mixing composite nanoparticles and composite microspheres at a mass ratio of 3 to 5:1. Through the combined effects of nano-reinforcement, microsphere toughening, and interfacial synergy, the mechanical properties and water resistance of the PHA coating film are improved while ensuring the processing stability and biocompatibility of the material.
[0005] The objective of this invention can be achieved through the following technical solutions: A PHA coating film comprises the following components in parts by weight: 50-80 parts PHA resin, 20-40 parts PBAT resin; 5-15 parts plasticizer, 3-10 parts modifying additive, 0.5-3 parts coupling agent, and 0.1-1 parts antioxidant; wherein the modifying additive is a mixture of composite nanoparticles and composite microspheres in a mass ratio of 3-5:1.
[0006] More preferably, the PHA resin is one or more of poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate), and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate); the coupling agent is one or more of silane coupling agent, titanate coupling agent, aluminate coupling agent, and zirconate coupling agent; the antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1 to 2:1; the hindered phenolic antioxidant is antioxidant 1010 or 1076, and the phosphite antioxidant is antioxidant 168.
[0007] More preferably, the method for preparing composite nanoparticles includes the following steps: A1. Add starch to deionized water and stir to gelatinize at 80~90℃ for 30~40 minutes to obtain starch paste; A2. Add maleic anhydride and potassium persulfate initiator to the starch paste and react at 60~70℃ for 2~3 hours to obtain maleic anhydride grafted starch. A3. Maleic anhydride-grafted starch and montmorillonite were added to deionized water and ultrasonically dispersed for 30-40 minutes. Then, the mixture was stirred and reacted at 80-90℃ for 1-2 hours. After centrifugation, washing, and drying, maleic anhydride-grafted starch-montmorillonite composite nanoparticles were obtained.
[0008] More preferably, the mass ratio of starch, maleic anhydride and initiator is 10:2~3:0.1~0.3, and the mass ratio of maleic anhydride-grafted starch to montmorillonite is 5~8:1.
[0009] More preferably, the preparation method of chitosan-g-polylactic acid-nanohydroxyapatite composite microspheres includes the following steps: B1. Dissolve chitosan in a 1%wt~2%wt acetic acid solution and stir until homogeneous to obtain a chitosan solution; B2. Add lactic acid monomer and stannous octoate catalyst to chitosan solution and react at 70~80℃ for 4~6h to obtain chitosan-polylactic acid copolymer; B3. Mix chitosan-polylactic acid copolymer with nano-hydroxyapatite, add to ethanol solution, sonicate for 20-30 min, and then spray dry to obtain chitosan-g-polylactic acid-nano-hydroxyapatite composite microspheres.
[0010] More preferably, the mass ratio of chitosan to lactic acid monomer is 1:3~5, the catalyst is stannous octoate, and its amount is 0.5%~1% of the mass of lactic acid monomer, and the mass ratio of chitosan-polylactic acid copolymer to nano-hydroxyapatite is 10:1~2.
[0011] A PHA-coated film and its preparation method, comprising the following steps: S1. According to the mass ratio, put PHA resin, PBAT resin, plasticizer, modifier, coupling agent and antioxidant into a high-speed mixer and mix at 90~110℃ for 20~25min to obtain a mixture. S2. The mixture is fed into a twin-screw extruder and melt-extruded and granulated at 160~190℃ to obtain PHA coating film masterbatch; S3. Place the PHA coating masterbatch into a blown film machine and blow film at 170~200℃ to obtain a PHA coating film.
[0012] An application of PHA coated film in food packaging and agricultural films. As a biodegradable material, PHA coated film shows great potential in the fields of food packaging and agricultural films.
[0013] The beneficial effects of this invention are: This invention utilizes the nano-reinforcing effect of composite nanoparticles and the microsphere-toughening effect of composite microspheres, synergistically in a 3-5:1 ratio, to significantly increase the tensile strength and elongation at break of the membrane material. The layered barrier of montmorillonite in the composite nanoparticles and the physical barrier of the composite microspheres form a dual protection, greatly enhancing water resistance. The interfacial bridging effect between the reactive groups of the composite nanoparticles and the composite microspheres solves the compatibility problem between traditional inorganic additives and organic resins, improving the uniformity of mixture dispersion and significantly enhancing component compatibility and processing stability. Furthermore, all raw materials used are bio-based or biodegradable, and the modification process does not introduce non-degradable components, meeting green environmental protection standards, avoiding white pollution, and aligning with the global trend towards green packaging materials. Detailed Implementation
[0014] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0015] Example 1: Preparation of a composite nanoparticle, comprising the following steps: A1. Add 100g of starch to 566mL of deionized water and stir at 85℃ for 35min to gelatinize and obtain starch paste; A2. Add 25g of maleic anhydride and 2g of potassium persulfate initiator to the starch paste, and react at 65℃ for 2.5h to obtain maleic anhydride-grafted starch. A3. Maleic anhydride-grafted starch and 18.5g montmorillonite were added to 4450mL of deionized water, ultrasonically dispersed for 35min, and then stirred at 85℃ for 1.5h. After centrifugation, washing and drying, maleic anhydride-grafted starch-montmorillonite composite nanoparticles were obtained.
[0016] Example 2: A method for preparing composite microspheres includes the following steps: B1. Dissolve 100g of chitosan in 70mL of acetic acid solution and stir well to obtain a chitosan solution; B2. Add 400g of lactic acid monomer and 2g of stannous octoate catalyst to the chitosan solution and react at 75℃ for 5h to obtain 500g of chitosan-polylactic acid copolymer. B3. Mix 500g of chitosan-polylactic acid copolymer with 75g of nano-hydroxyapatite, add to ethanol solution, sonicate for 25min, and then spray dry to obtain chitosan-g-polylactic acid-nano-hydroxyapatite composite microspheres.
[0017] Example 3: A PHA coating film comprising the following components in parts by weight: The mixture comprises 50 parts PHA resin, 40 parts polybutylene adipate-butylene terephthalate resin, 5 parts tributyl citrate, 10 parts modifying additives, 0.5 parts titanate coupling agent, and 1 part antioxidant. The antioxidant is a 1:1 mass ratio mixture of antioxidant 1010 and antioxidant 168. The modifying additive is a 3:1 mass ratio mixture of composite nanoparticles and composite microspheres. The composite nanoparticles are maleic anhydride-grafted starch-montmorillonite prepared in Example 1, and the composite microspheres are chitosan-g-polylactic acid-nano hydroxyapatite prepared in Example 2.
[0018] The above-mentioned method for preparing the PHA-coated film includes the following steps: S1. According to the mass ratio, put PHA resin, PBAT resin, plasticizer, modifier, coupling agent and antioxidant into a high-speed mixer and mix at 90°C for 25 minutes to obtain a mixture. S2. The mixture is fed into a twin-screw extruder, melt-extruded and granulated at 160°C to obtain PHA coating film masterbatch; S3. Place the PHA coating masterbatch into a blown film machine and blow it at 200°C to obtain a PHA coating film.
[0019] Example 4: A PHA coating film comprising the following components in parts by weight: The mixture comprises 65 parts PHA resin, 30 parts polybutylene adipate-butylene terephthalate resin, 10 parts tributyl acetylacetonate mixed with epoxidized soybean oil in a 1:1 ratio, 6 parts modifying additives, 2 parts silane coupling agent, and 0.5 parts antioxidant. The antioxidant is a mixture of antioxidant 1076 and antioxidant 168 in a 1.5:1 mass ratio. The modifying additive is a mixture of composite nanoparticles and composite microspheres in a 4:1 mass ratio. The composite nanoparticles are maleic anhydride-grafted starch-montmorillonite prepared in Example 1, and the composite microspheres are chitosan-g-polylactic acid-nano hydroxyapatite prepared in Example 2.
[0020] The above-mentioned method for preparing the PHA-coated film includes the following steps: S1. According to the mass ratio, put PHA resin, PBAT resin, plasticizer, modifier, coupling agent and antioxidant into a high-speed mixer and mix at 100°C for 22 minutes to obtain a mixture. S2. The mixture is fed into a twin-screw extruder, melt-extruded and granulated at 175°C to obtain PHA coating film masterbatch; S3. Place the PHA coating masterbatch into a blown film machine and blow the film at 185°C to obtain a PHA coating film.
[0021] Example 5: A PHA coating film comprising the following components in parts by weight: The mixture comprises 80 parts PHA resin, 20 parts polybutylene adipate-butylene terephthalate resin, 15 parts epoxidized soybean oil, 3 parts modifying additives, 3 parts aluminate coupling agent, and 0.1 parts antioxidant. The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 at a mass ratio of 2:1. The modifying additive is a mixture of composite nanoparticles and composite microspheres at a mass ratio of 5:1. The composite nanoparticles are maleic anhydride-grafted starch-montmorillonite prepared in Example 1, and the composite microspheres are chitosan-g-polylactic acid-nano hydroxyapatite prepared in Example 2.
[0022] The above-mentioned method for preparing the PHA-coated film includes the following steps: S1. According to the mass ratio, PHA resin, PBAT resin, plasticizer, modifier, coupling agent and antioxidant are put into a high-speed mixer and mixed at 110°C for 20 minutes to obtain a mixture; S2. The mixture is put into a twin-screw extruder, melt-extruded and granulated at 190°C to obtain PHA coating film masterbatch. S3. Place the PHA coating masterbatch into a blown film machine and blow film at 170°C to obtain a PHA coating film.
[0023] Comparative Example 1: A PHA coated film, with the same composition and preparation as in Example 4, except that maleic anhydride-grafted starch-montmorillonite composite nanoparticles were not added.
[0024] Comparative Example 2: A PHA coated film, with the same composition and preparation as Example 4, except that the modified additive chitosan-g-polylactic acid-nanohydroxyapatite composite microspheres were not added.
[0025] Performance testing The PHA coated films prepared in Examples 3-5 and Comparative Examples 1-2 were tested for changes in tensile strength, elongation at break, and water resistance under different conditions. The tensile strength and elongation at break were tested according to GB / T1040.3-2006, and the test strips were all dumbbell-shaped. The water resistance was tested according to GB / T1034-2008, and the test strips were rectangular. The data obtained are shown in Table 1 below.
[0026] Table 1 Performance Testing of PHA Coated Film
[0027] As can be seen from the data in Table 1, the PHA coating films in Examples 3-5 of the present invention exhibit high tensile strength and elongation at break in various performance tests, but low water resistance. Among them, Comparative Examples 1 and 2, without the addition of modified additives maleic anhydride-grafted starch-montmorillonite composite nanoparticles and chitosan-g-polylactic acid-nanohydroxyapatite composite microspheres, respectively, show significantly reduced tensile strength and elongation at break, but increased water resistance. Among them, the formulation in Example 4 is the optimal combination. The modified additives maleic anhydride-grafted starch-montmorillonite composite nanoparticles and chitosan-g-polylactic acid-nanohydroxyapatite composite microspheres prepared by the present invention through a specific process work synergistically to significantly improve the mechanical properties and water resistance of the PHA coating film.
[0028] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0029] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A PHA coating film, characterized in that, The product comprises the following components by weight: 50-80 parts of PHA resin, 20-40 parts of PBAT resin; 5-15 parts of plasticizer, 3-10 parts of modifying additive, 0.5-3 parts of coupling agent, and 0.1-1 parts of antioxidant; wherein the modifying additive is a mixture of composite nanoparticles and composite microspheres at a mass ratio of 3-5:
1. The composite nanoparticles are obtained by grafting maleic anhydride onto starch and then combining it with nano-montmorillonite. The composite microspheres are obtained by graft copolymerization of chitosan and polylactic acid and then combined with nano-hydroxyapatite.
2. The PHA coating film according to claim 1, characterized in that, The PHA resin is one or more of poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-co-3-hydroxyvalerate), and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate); the plasticizer is one or more of tributyl citrate, acetylated tributyl citrate, and epoxidized soybean oil; the coupling agent is one or more of silane coupling agents, titanate coupling agents, aluminate coupling agents, and zirconate coupling agents; the antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1 to 2:1; the hindered phenolic antioxidant is antioxidant 1010 or 1076, and the phosphite antioxidant is antioxidant 168.
3. The PHA coating film according to claim 1, characterized in that, The method for preparing the composite nanoparticles includes the following steps: A1. Add starch to deionized water and stir to gelatinize at 80~90℃ for 30~40 minutes to obtain starch paste; A2. Add maleic anhydride and potassium persulfate initiator to the starch paste and react at 60~70℃ for 2~3 hours to obtain maleic anhydride grafted starch. A3. Maleic anhydride-grafted starch and montmorillonite were added to deionized water and ultrasonically dispersed for 30-40 minutes. Then, the mixture was stirred and reacted at 80-90℃ for 1-2 hours. After centrifugation, washing, and drying, maleic anhydride-grafted starch-montmorillonite composite nanoparticles were obtained.
4. The PHA coating film according to claim 3, characterized in that, The mass ratio of starch, maleic anhydride and initiator is 10:2~3:0.1~0.3, and the mass ratio of maleic anhydride-grafted starch to montmorillonite is 5~8:
1.
5. The PHA coating film according to claim 1, characterized in that, The method for preparing the composite microspheres includes the following steps: B1. Dissolve chitosan in a 1wt%~2wt% acetic acid solution and stir until homogeneous to obtain a chitosan solution; B2. Add lactic acid monomer and stannous octoate catalyst to chitosan solution and react at 70~80℃ for 4~6h to obtain chitosan-polylactic acid copolymer; B3. Mix chitosan-polylactic acid copolymer with nano-hydroxyapatite, add to ethanol solution, sonicate for 20-30 min, and then spray dry to obtain chitosan-g-polylactic acid-nano-hydroxyapatite composite microspheres.
6. The PHA coating film according to claim 5, characterized in that, The mass ratio of chitosan to lactic acid monomer is 1:3~5, and the catalyst is stannous octoate, with the amount of stannous octoate being 0.5%~1% of the mass of lactic acid monomer.
7. A method for preparing a PHA coated film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. According to the mass ratio, put PHA resin, PBAT resin, plasticizer, modifier, coupling agent and antioxidant into a high-speed mixer and mix at 90~110℃ for 20~25min to obtain a mixture. S2. The mixture is fed into a twin-screw extruder and melt-extruded and granulated at 160~190℃ to obtain PHA coating film masterbatch; S3. Place the PHA coating masterbatch into a blown film machine and blow film at 170~200℃ to obtain a PHA coating film.
8. The application of a PHA-coated film as described in any one of claims 1 to 6 in food packaging and agricultural films, characterized in that, It has good mechanical properties and water resistance, as well as processing stability and biocompatibility.